The health needs of the black elderly population in certain areas of rural and urban Kwazulu - M. Kumalo; L. R. Uys (AOSIS, 1990)
The health needs of Black elderly in rural and urban KwaZulu was investigated through a survey. Interviews with 240 elderly was done, looking at the first and second level of the health facilities plan, as well as social support and health indicators. It was found that urban elderly are generally better off than rural elderly and a profile of need is described.